Procedure of appeal of decisions of the Higher Qualification Commission and the Higher Council of Justice of Ukraine in the cases of liability of judges - Овчаренко, О. М. (Problems of legality, 2013)
The author analyzes procedure f appeal of decisions of the Higher Qualification Commission and the Higher Council of Justice of Ukraine when a judge is brought under legal responsibility. Some propositions on improvement of the legislation, that regulates this procedure are presented.